PENGARUH LEVERAGE OPERASI DAN LEVERAGE KEUANGAN TERHADAP LABA PER LEMBAR SAHAM (Studi kasus Pada Perusahaan Tekstil yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Rifa Ariana Ningtyas; Ronny Malavia Mardani; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This8study aimed konstan to find out the konstan effects the variables of Operating Leverage and Financial Leverage partially on Earnings per Share. The data used in the study were secondary data obainted from the Indonesia Stock Exchange, namely the financial reports from 2014-2016. The research population comparised 539 companies which had konstan been and were konstan still listed konstan in the Indonesia konstan Stock Exchange konstan in 2014-2016 periods. The sample was selected by means konstan of the purposive konstan sampling technique and 14 the textile companies konstan were included in the sampel. The data analysis technique was multiple linear regression analysis. Based on the results of the data analysis, partially the Degree of Operating Leverage had a positive and not significant affect the Earnings per Share, and the Degree of Financial Leverage had a positive and significant affect on the Earnings Per Share. The value of the adjusted R-square was 0,107 indicating that the independent variable was capable of explaining the variance in the dependent variable by 10,7%, and the konstan remaining 89,3% was explained by other variables outside the research model. The multiple konstan linear konstan regression equation in the study could be formulated as follows: Y = 1,9998 + 0,008 DOL + 0,158 DFL + eKeywords: Operating Leverage, Financial Leverage, Earnings Per Share.